دلالات أسماء الفاعلين فى كتاب رياض الصالحين : دراسة وصفية تحليلية /‏ - Nurul Hanilah Mohd Ismath
The objective of this thesis is to study the linguistic case of Ism al-Fa'il that indicates the tenses, namely past, present, and future tenses as well as other grammatical functions in the book of Riyad al-Salihin. In this regard, the study tries to identify certain factors which lead to various indications of Ism al- Fa'il in terms of grammatical context. The researcher focuses on the analytical method to visualize the indications of Ism al- Fa'il included in this book. After this observation, the study found that most Ism al- Fa'il play the role in indicating several grammatical functions, for example noun, adjective, and proper noun followed by tenses; present, future, and last but not least past. Such indications are based on the reference of the context used in particular sentences.